2018
DOI: 10.1016/j.str.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanistic Insights into Drosophila DHX36-Mediated G-Quadruplex Unfolding: A Structure-Based Model

Abstract: Helicase DHX36 plays essential roles in cell development and differentiation at least partially by resolving G-quadruplex (G4) structures. Here we report crystal structures of the Drosophila homolog of DHX36 (DmDHX36) in complex with RNA and a series of DNAs. By combining structural, small-angle X-ray scattering, molecular dynamics simulation, and single-molecule fluorescence studies, we revealed that positively charged amino acids in RecA2 and OB-like domains constitute an elaborate structural pocket at the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 59 publications
4
32
0
Order By: Relevance
“…When no nucleotide is bound in the active site and the two RecA domains take up the open conformation, K445 is the side chain that is closest to the first base of the five RNA nucleotides in the RNA channel. Therefore, in homologous DEAH/RHA helicases, the analogous residues form hydrogen bonds to the first base (8,(11)(12)(13). Although the conformational change is relatively small, we consistently observed it in both structures of DHX15 (apo and ADP-bound).…”
Section: K E Q H K R E G L G L D V E Sc Pfa1 720 N E N I G R R M supporting
confidence: 56%
See 2 more Smart Citations
“…When no nucleotide is bound in the active site and the two RecA domains take up the open conformation, K445 is the side chain that is closest to the first base of the five RNA nucleotides in the RNA channel. Therefore, in homologous DEAH/RHA helicases, the analogous residues form hydrogen bonds to the first base (8,(11)(12)(13). Although the conformational change is relatively small, we consistently observed it in both structures of DHX15 (apo and ADP-bound).…”
Section: K E Q H K R E G L G L D V E Sc Pfa1 720 N E N I G R R M supporting
confidence: 56%
“…One explanation could come from comparing RecA positions in previous DEAH structures without G-patch. Here, the conformational extremes of apo vs. nucleotide-bound state were much more pronounced, and the two RecA domains relaxed to significantly more open conformations in the apo state (8,(11)(12)(13). We judged the distance between RecA1 and RecA2 by measuring the spacing between the C α of two conserved residues that sandwich the nucleotide in the active site, an Arg in RecA1 (R204 in hsDHX15; SI Appendix, Fig.…”
Section: The G-patch Can Follow Reca2 Transitions Required For Nucleomentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently DEAH-box helicases demonstrating substrate preference have been reported. Examples include Drosophila DHX9 (also known as MLE), which preferentially binds uracil-rich RNA [50], and Drosophila DHX36, which has a preference for guanine-rich DNA [55]. To investigate whether DHX8 has any sequence specificity, we first confirmed that DHX8 is an RNA-specific helicase by showing that a poly(dA) 10 DNA strand could not displace Cy5-poly(A) 10 from DHX8 in the presence of ADP-AlF x ( Figure 4A).…”
Section: Dhx8 Is An Ntpase With Rna-unwinding Capabilitymentioning
confidence: 99%
“…DHX8Δ547 adopts a pyramidal-like structure with the two N-terminal RecA domains and the C-terminal ratchet-like and OB-fold domains on opposite sides of the putative DHX8 RNA-binding tunnel, and the C-and N-terminal domains connected by the WH domain. A 26 Å long antiparallel β-hairpin, characteristic of the DEAH helicase family [25,26,35,50,55], extends from RecA2 and interacts with a C-terminal region between the WH and OB-fold domains. The ADP molecule bound in the ATP-binding site between the DHX8 RecA1 and RecA2 domains has a binding mode similar to the one observed for Prp43 and DHX15 [25,29,56].…”
Section: The Structure Of Dhx8δ547 Reveals Unexpected Flexibility In mentioning
confidence: 99%